THE INDO-PACIFIC TURN IN THE U.S. FOREIGN POLICY: A GEOPOLITICAL APPROACH FROM NEOCLASSICAL REALISM - VIDAL PÉREZ, Esteban (Journal of the Spanish Institute for Strategic Studies, 2023)
This article aims to develop a geopolitical explanation of the Indo-Pacific turn in U.S. foreign policy. To do so, it resorts to the theoretical framework of neoclassical realism and its different levels of analysis. It focuses on the interactions between the systemic pressures and the perception of the American elite from a spatial standpoint. The geographic mental maps are the analytical tool used for this purpose because it helps understand how U.S. statesmen perceive the international geopolitical environment and respond to external pressures. The article asks what role these mental maps developed in the new geopolitical orientation in U.S. foreign policy. The answer to this question is that the American elite understood the rise of China through their geographic mental maps, which has led them to consider it a threat to the U.S. international position. As a result, the U.S. has focused its foreign policy on the Indo-Pacific region. In order to test this hypothesis, the study resorts to a qualitative methodology by reviewing the literature available in neoclassical realism and geopolitics, as well as the contributions of foreign policy advisors and official statements of U.S. institutions and decision-makers.